Algeria: From One Revolution to the Other? : The Metamorphosis of the State-Regime Complex - Hachemaoui, Mohammed (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2020)
A dominant narrative describes the postcolonial Algerian trajectory as a “revolution” which has alternately experienced a “Party-state”, the “Islamist peril”, a “civil war” then an “autocracy”—the “crisis” of the latter precipitating a “popular uprising” that caused the fall of the “raïs” and imposed a “transition”. Breaking with the doxa, this study establishes that the domination, resulting from the counter-revolution of the 1950s, is based on a praetorian state-regime complex. The critical sequence that starts with the military coup of 1992 is less a “civil war” than a fierce neoliberal restructuring giving rise to the “reinvention of tradition” of the garrison state as “organized crime”. Drawing a “strategic learning” from the success of the praetorian counterrevolution orchestrated by the Egyptian secret police in 2013, the powerful Algerian deep state has been arranging the anti-Bouteflika V street demonstrations. Beyond an apparent radicalism, the hirak contributes to freezing the authoritarian status quo: anti-political, it operates a structural avoidance of the conflicts at work in the shade of praetorian neoliberalism. Celebrating brotherhood with the army, the late counter-revolution has increased the “caging” of the Algerian people. Algérie : d’une révolution à l’autre ? Les métamorphoses du complexe État-régime Un récit dominant décrit la trajectoire postcoloniale algérienne comme une « révolution » qui a connu tour à tour le « Parti-État », le « péril islamiste », une « guerre civile » puis une « autocratie », la « crise » de cette dernière précipitant un « soulèvement populaire » provoquant la chute du « raïs » et imposant une « transition ». En rupture avec la doxa, cette étude établit que la domination politique, issue de la contre-révolution prétorienne des années 1950, s’appuie sur un complexe État-régime prétorien. La séquence historique qui s’ouvre avec le coup d’État militaire de janvier 1992 est moins une « guerre civile » qu’une violente néolibéralisation prétorienne, nécessitant la réinvention de la tradition de l’État-garnison comme « crime organisé ». Tirant un « enseignement stratégique » du succès de la gigantesque mobilisation orchestrée par la police politique égyptienne contre le président élu Mohamed Morsi en 2013, la puissante police secrète algérienne orchestre, canalise et encadre les manifestations de rue anti-Bouteflika V. Sous une apparente radicalité, ledit hirak contribue à figer le statu quo autoritaire : antipolitique, il opère un évitement structurel des conflits qui travaillent la domination néoprétorienne et néolibérale. Célébrant la fraternité avec l’armée, cette contre-révolution pacifique achève de renforcer la « mise en cage » du peuple.